Temperature Monitoring and Fan Control System for Breast Milk Storage Coolbox Based on Arduino Uno - Haryanti, Tri; Pamungkas, Anugrah; Kurnianingtyas, Rahajeng; Fatwasauri, Icha (Institute Of Advanced Knowledge and Science, 2025)
Breast milk is the main source of nutrition for infants and is highly susceptible to spoilage if not stored at the right temperature. This system uses temperature sensors to monitor the thermal conditions in the storage cabin and automatically control the cooling fan to maintain the ideal temperature for breast milk storage. Test results show that the thermoelectric-based cooling system works optimally in conditions without products, with an initial temperature of 31.3°C that decreases to 2.3°C within 70 minutes. However, in conditions with breast milk products, the initial temperature of 35.3°C could only be reduced to 5.4°C within 120 minutes. This difference indicates that the presence of the product provides an additional thermal load that slows down the cooling process. Therefore, a responsive automatic temperature control system and better thermal insulation are needed to maintain the breast milk storage temperature stably around 4°C. This system is expected to maintain the quality of breast milk during storage and support users' needs in maintaining stable storage temperature efficiently.